DEVELOPING POP-UP MEDIA BASED ON LOCAL WISDOM FOR GRADE IV OF ELEMENTARY SCHOOL ON THEME 8 DAERAH TEMPAT TINGGALKU - Noor Khamidah; Sri Utaminingsih; Mohammad Kanzunnudin (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
This study aimed to develop pop-up learning media based on local wisdom for grade IV elementary schools on theme 8 “Daerah Tempat Tinggalku” as well as to test the effectiveness of the developed media. The research method was research and development (Research and Development) according to Borg & Gall. This research was conducted in 3 elementary schools, at grade IV Mejobo Kudus in November 2020. The research was conducted in seven steps which were divided into 4 stages of research, namely preliminary research, planning and media development, validation, revision, and evaluation, and media implementation. Data in this study were collected through observation, interviews, and questionnaires, as well as tests. Based on the results of N-Gain analysis showed that the experimental class got an average gain score of 0.4072 with the medium category and the control class got an average gain score of 0.0193 with the low category. The developed media was validated by experts and peers. It was concluded that Pop Up media based on local wisdom was effective and worthy to be applied in improving the learning outcomes of fourth grade elementary school students in Kabupaten Kudus.